2022
DOI: 10.1093/hropen/hoac054
|View full text |Cite
|
Sign up to set email alerts
|

The effect of frozen embryo transfer regimen on the association between serum progesterone and live birth: a multicentre prospective cohort study (ProFET)

Abstract: STUDY QUESTION What is the association between serum progesterone levels on the day of frozen embryo transfer (FET) and the probability of live birth in women undergoing different FET regimens? SUMMARY ANSWER Overall, serum progesterone levels <7.8 ng/ml were associated with reduced odds of live birth, although the association between serum progesterone levels and the probability of live birth appeared to vary accordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 57 publications
0
23
0
Order By: Relevance
“…The timing of serum progesterone measurements varied widely from the day of ET (seven studies) 66,67,70-74 and after ET (two studies) 68,69 . Three studies used vaginal suppositories 70,71,73 , two studies used intramuscular injections 67,69 and four studies used a combination of progesterone support 68,70,72,74 . Three studies 69,73,74 reported single progesterone threshold level (<7.8ng/ml, <9.8ng/ml and <13.15ng/ml) and the remaining six studies 66-68,70-72 reported progesterone value according to quartiles or percentiles.…”
Section: At Luteal Phasementioning
confidence: 99%
See 1 more Smart Citation
“…The timing of serum progesterone measurements varied widely from the day of ET (seven studies) 66,67,70-74 and after ET (two studies) 68,69 . Three studies used vaginal suppositories 70,71,73 , two studies used intramuscular injections 67,69 and four studies used a combination of progesterone support 68,70,72,74 . Three studies 69,73,74 reported single progesterone threshold level (<7.8ng/ml, <9.8ng/ml and <13.15ng/ml) and the remaining six studies 66-68,70-72 reported progesterone value according to quartiles or percentiles.…”
Section: At Luteal Phasementioning
confidence: 99%
“…Data from various threshold values were summarised in Supplementary Table S5. In both natural cycle and medicated FET cycle, Melo et al 74 reported LBR, CPR and MR as summarised in Supplementary Table S6.…”
Section: B Luteal Phasementioning
confidence: 99%
“…The present article by Melo et al is new in that it studies the links between serum progesterone levels and the outcomes in all forms of treatment used for priming FET ( Melo et al , 2022 ). This also includes the situation when subcutaneous progesterone (Lubion ® ) 25 mg BID is used exclusively ( Melo et al, 2022 ).…”
mentioning
confidence: 99%
“…The present article by Melo et al is new in that it studies the links between serum progesterone levels and the outcomes in all forms of treatment used for priming FET ( Melo et al , 2022 ). This also includes the situation when subcutaneous progesterone (Lubion ® ) 25 mg BID is used exclusively ( Melo et al, 2022 ). In this particular case, the study shows a biphasic relationship between serum progesterone levels and FET outcome with a sharp decrease in outcome when serum progesterone exceeds 16.3 ng/ml on the day of ET ( Melo et al , 2022 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation